Spontaneous stomach rupture: Tension pneumoperitoneum - Carriquiry, Luis A.; Baldizán, Jorge W.; Cazabán, Luis A. (Cirugía del Uruguay, 1978)
For the first time a case of spontaneous rupture of the stomach occurs in our country. The term is defined; etiologic circumstances are analyzed; clinical picture is described -entailing pain, distention and pneumoperitoneum- and therapeutical tactics proposed: suture of opening and decompressive gastrostomy.